“X中的X”格式句法语义分析 =The Analysis of Syntactic and Semantic on “X Zhongde X” /Fan Zhong-yuan;College of Arts,Guangxi Normal University. - Fan, Zhong-Yuan.
In the pattern of X zhongde X,X is mainly a noun.And it can also be an adjective,a verb,or an adverb etc. "X zhongde X" is usually used as an object.But it can also be used as a subject,a predicate,an attributive,an adverbial,a complement,a clause,or an independent sentence.The referent objects of X1 and X2 are the collective members of the same semantic properties.X1 and X2 are of different semantic magnitude order. "X2" belongs to the highlight portions of the magnitude order.The magnitude order between "X1 and X2" can be divided into two-layer one and multilayer one